GAMBARAN POLA MENYUSUI IBU PADA NEONATUS: STUDI DESKRIPTIF: OVERVIEW OF PATTERNS IN NEONATAL NURSING MOTHERS: DESCRIPTIVE STUDY - Resiyanthi, Ni Komang Ayu; Ekawati, Heni; Sudiletari, Anak Agung Ayu; Dewi, Gusti Ayu Made Purnama (Bali Medika Jurnal, 2019)
Knowledge is the basis of a mother for exclusive nursing and nursing. This study aims to identify maternal breastfeeding patterns in neonates. This research is a descriptive study with a quantitative approach. The sampling method was purposive sampling in 130 mothers. Data analysis with univariate analysis. The results showed that most respondents had good knowledge about breastfeeding patterns in neonates as many as 66 people (50.77%). The distribution of knowledge to most respondents answered correctly on questions about general knowledge about the nursing process as many as 49 people (37.69%), the frequency of breastfeeding as many as 73 people (56.15%), the frequency of breastfeeding as many as 73 people (56.15% ), the position of the mother and baby during the breastfeeding process as many as 50 people (38.46%), factors affecting breastfeeding for as many as 40 people (30.77%), factors that influence the pattern of breastfeeding as many as 38 people (29.23%) . Recommendation: Mothers are more active in finding information about good breastfeeding patterns and also good nutrition so that the milk production is better and the production of breast milk is more. So that it can meet the needs of infants in their growth and development.